2009
DOI: 10.1007/s10750-009-9825-6
|View full text |Cite
|
Sign up to set email alerts
|

What confines an annual plant to two separate zones along coastal topographic gradients?

Abstract: We investigated the roles of flooding, salinity, and plant competition in creating a bimodal zonation pattern of the marsh dominant annual plant, Suaeda salsa, along coastal topographic gradients on the Pacific coast of northern China. In two consecutive years, we manipulated salinity and flooding, salinity, and competition for S. salsa seedlings that had been transplanted into the mudflat, the high marsh, and the upland, respectively. S. salsa plants that had been transplanted into the mudflat were completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 45 publications
0
42
0
Order By: Relevance
“…This emphasizes the essence of the physiological-ecologicalamplitude concept, and extends it to stress gradients biotically created by a third species. Furthermore, by showing that S. salsa dominating saline marshes was competitively restricted from the low-salinity upland, our study suggests that this concept may be applicable to broad stress gradients that encompass coastal marsh and terrestrial habitats (also see He et al 2009). …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This emphasizes the essence of the physiological-ecologicalamplitude concept, and extends it to stress gradients biotically created by a third species. Furthermore, by showing that S. salsa dominating saline marshes was competitively restricted from the low-salinity upland, our study suggests that this concept may be applicable to broad stress gradients that encompass coastal marsh and terrestrial habitats (also see He et al 2009). …”
Section: Discussionmentioning
confidence: 67%
“…Fieldwork was conducted at upper elevations of a coastal marsh-upland ecosystem in the Yellow River Delta, northeast China (see He et al [2009] for a map). The climate is warm-temperate.…”
Section: Study Site and Speciesmentioning
confidence: 99%
“…The lower limits of plants are thought to be determined by physical stress, while the upper limits of plants are determined by interspecific plant competition. This simple community assembly model has been tested in California (Pennings & Callaway, 1992), Spain (Castellanos, Figueroa, & Davy, 1994;Castillo, Fernandez-Baco, Castellanos, & Davy, 2000), Brazil (Costa, Marangoni, & Azevedo, 2003), China (He, Cui, Bertness, & An, 2012;He et al, 2009), Argentina (Alberti et al, 2010;Idaszkin, Bortolus, & Bouza, 2011, and Chile (Farina, Silliman & Bertness, 2009). …”
mentioning
confidence: 99%
“…Lines a-e, divisions between mudflat and Spartina low marsh, Spartina low marsh and Suaeda low marsh, Suaeda low marsh and high marsh, high marsh and terrestrial border, and terrestrial border and upland, respectively. Refer to He et al (2009a) for the location of the study site on the western Pacific coast estuary, becoming a dominant species in these habitats and is moving up rapidly. Other plant species including Salicornia europaea, Scripus spp., and Juncus spp.…”
Section: Study Sitementioning
confidence: 99%
“…In a Californian salt marsh, Pennings and Callaway (1992) indicated that although flooding, soil salinity, and competition all interacted to determine plant zonation patterns, the relative importance of these factors differed at different elevations. Moreover, the precise roles of the two main physical stressors, salinity and flooding, in mediating plant zonation were also suggested to vary with elevation in a Chinese salt marsh (He et al 2009a).…”
Section: Introductionmentioning
confidence: 99%